Self-powered intracellular nanogenerator attenuates inflammatory osteolysis through mitochondrial MRS2/Mg2+-mediated macrophage repolarization and osteoclastogenesis inhibition - Jiyuan Zuo; Qining Guo; Youzhun Fan; Xiaobin Fu; Fengyuan Zhang; Xiaojing Zhu; Chengyun Ning; Yuanyuan Kong; Peng Yu; Jianmao Zheng (Materials Today Bio)
Inflammatory bone resorption is present in common oral and maxillofacial diseases. Macrophages play a crucial role in the inflammatory process of bone. It has been shown that M1 macrophages cause bone homeostasis and bone resorption disorders, and M2 macrophage-related cytokines inhibit osteoclast generation. To inhibit inflammatory bone resorption, a method that promotes M2 polarization and inhibits M1 polarization and osteoclastogenesis should be found. Studies have found that the mitochondrial membrane potential of macrophage increases during M2 differentiation, but decreases during M1 differentiation and osteoclast differentiation. Therefore, we hypothesized that it might be possible to use electric fields to regulate macrophage polarization and osteoclast differentiation. Piezoelectric materials have been shown to be a safe and effective material that can form piezoelectric potentials, but the role of piezoelectric nanomaterials and nano-electric fields in macrophage M2 differentiation and osteoclastogenesis remains to be investigated. Thus, in this study, polarized piezoelectric nanomaterial BaTiO3 (pBTO) is applied to macrophage cells to provide wireless intracellular electric field. Wireless intracellular electric field from pBTO is proved to regulate mitochondrial Mg2+ via MRS2, regulate mitochondrial metabolism, induce macrophage M2 polarization, and inhibit M1 differentiation and osteoclast differentiation in vitro. Moreover, calvarial inflammatory osteolysis mouse model reveal that pBTO inhibit inflammatory bone resorption by modulating macrophage polarization and osteoclastogenesis via mitochondrial MRS2/Mg2+. These results indicates that pBTO may be a potential approach to treat inflammatory or infective osteolysis through “nanoelectric field - Mg2+ transport - mitochondrial metabolism” signal axis in a convenient, wireless and non-invasive way.